2019
DOI: 10.1128/iai.00276-19
|View full text |Cite
|
Sign up to set email alerts
|

Development of Opsonic Mouse Monoclonal Antibodies against Multidrug-Resistant Enterococci

Abstract: Multidrug-resistant enterococci are major causes of hospital-acquired infections. Immunotherapy with monoclonal antibodies (MAbs) targeting bacterial antigens would be a valuable treatment option in this setting. Here, we describe the development of two MAbs through hybridoma technology that target antigens from the most clinically relevant enterococcal species. Diheteroglycan (DHG), a well-characterized capsular polysaccharide of Enterococcus faecalis, and the secreted antigen A (SagA), an immunogenic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, the mAb against DHG exhibited lower killing compared to the polyclonal serum raised against the same antigen, revealing a variability in the presence and exposure of the recognizable epitope between the strains [126]. A combination therapy using antibodies that target a variety of antigenic epitopes would provide broad coverage and overcome the lack of diagnostic methods [126]. Similar strategies are being explored against other types of diseases, e.g., cancer, and could also be implemented in infectious diseases [133,134].…”
Section: Prospects and Pitfalls In The Development Of Immunotherapiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, the mAb against DHG exhibited lower killing compared to the polyclonal serum raised against the same antigen, revealing a variability in the presence and exposure of the recognizable epitope between the strains [126]. A combination therapy using antibodies that target a variety of antigenic epitopes would provide broad coverage and overcome the lack of diagnostic methods [126]. Similar strategies are being explored against other types of diseases, e.g., cancer, and could also be implemented in infectious diseases [133,134].…”
Section: Prospects and Pitfalls In The Development Of Immunotherapiesmentioning
confidence: 98%
“…Passive immunotherapy using mAbs is an emerging field with many promising candidates to fight these health threats, either by replacing the common antibiotic therapy or by co-administration with antibiotics [125,126]. mAbs are also of great importance for the development of chemically defined vaccines by solving the bottleneck of epitope identification [127].…”
Section: Prospects and Pitfalls In The Development Of Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalfopoulou et al provided data on two highly specific antibodies directed against the polysaccharide and carrier protein. Both antibodies showed good opsonic killing against target bacterial strains in upwards of 40% for E. faecium and 90% for E. faecalis respectively [ 140 ]. Romero-Saavedra et al showed similar results with antibodies against the corresponding conjugate, as well as against the respective protein and carbohydrate antigens.…”
Section: Conjugate Vaccine Antigensmentioning
confidence: 99%
“…Given the prevalence of enterococcal infections and the treatment challenges, there is an urgent need to develop new approaches to treat or prevent these infections. Immunotherapies, among other options, represent a promising avenue of research [5].…”
Section: Introductionmentioning
confidence: 99%